Selective Axonal Expression of the Kv1 Channel Complex in Pre-myelinated GABAergic Hippocampal Neurons - Bonetto, Giulia; Hivert, Bruno; Goutebroze, Laurence; Karagogeos, Domna; Crépel, Valérie; Faivre-Sarrailh, Catherine (Frontiers in Cellular Neuroscience, 2019)
IIn myelinated fibers, the voltage-gated sodium channels Nav1 are concentrated at the nodal gap to ensure the saltatory propagation of action potentials. The voltage-gated potassium channels Kv1 are segregated at the juxtaparanodes under the compact myelin sheath and may stabilize axonal conduction. It has been recently reported that hippocampal GABAergic neurons display high density of Nav1 channels remarkably in clusters along the axon before myelination (Freeman et al., 2015). In inhibitory neurons, the Nav1 channels are trapped by the ankyrinG scaffold at the axon initial segment (AIS) as observed in pyramidal and granule neurons, but are also forming “pre-nodes”, which may accelerate conduction velocity in pre-myelinated axons. However, the distribution of the Kv1 channels along the pre-myelinated inhibitory axons is still unknown. In the present study, we show that two subtypes of hippocampal GABAergic neurons, namely the somatostatin and parvalbumin positive cells, display a selective high expression of Kv1 channels at the AIS and all along the unmyelinated axons. These inhibitory axons are also highly enriched in molecules belonging to the juxtaparanodal Kv1 complex, including the cell adhesion molecules (CAMs) TAG-1, Caspr2 and ADAM22 and the scaffolding protein 4.1B. Here, taking advantage of hippocampal cultures from 4.1B and TAG-1 knock-out mice, we observed that 4.1B is required for the proper positioning of Caspr2 and TAG-1 along the distal axon, and that TAG-1 deficiency induces alterations in the axonal distribution of Caspr2. However, the axonal expression of Kv1 channels and clustering of ankyrinG were not modified. In conclusion, this study allowed the analysis of the hierarchy between channels, CAMs and scaffolding proteins for their expression along hippocampal inhibitory axons before myelination. The early steps of channel compartmentalization preceding myelination may be crucial for stabilizing nerve impulses switching from a continuous to saltatory conduction during network development.